2019
DOI: 10.1186/s40249-019-0608-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction patterns of Japanese encephalitis incidence following vaccine introduction into long-term expanded program on immunization in Yunnan Province, China

Abstract: BackgroundJapanese encephalitis (JE) is a leading cause of childhood viral encephalitis both at global level and in China. Vaccination is recommended as a key strategy to control JE. In China most JE cases have been reported in southwest provinces, which include Yunnan. In this study, we quantify the epidemiological shift of JE in Yunnan Province from 2005 to 2017, covering before and after the introduction of JE vaccination into routine Expanded Program on Immunization (EPI) in 2007.MethodsWe used routinely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A study conducted in Yunnan province, China, showed a decrease in incidence rate per 100 000 population, from 1.16 in 2009 to 0.17 in 2017, with the introduction of a JE vaccination programme. ( 11 ) However, as the virus is maintained in animal reservoirs, non-immune individuals remain at risk of infection. In the Philippines, the JE vaccine is not widely available to the public and is only available through private clinics.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Yunnan province, China, showed a decrease in incidence rate per 100 000 population, from 1.16 in 2009 to 0.17 in 2017, with the introduction of a JE vaccination programme. ( 11 ) However, as the virus is maintained in animal reservoirs, non-immune individuals remain at risk of infection. In the Philippines, the JE vaccine is not widely available to the public and is only available through private clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the efforts to control JE in India and other JEV endemic Asian countries are focused on widespread vaccination programs. The disease is preventable by vaccination and vaccination drives which have shown significant results [ 174 ]. However, the prevalence of neurological complications related to JEV remains significantly high, with death rate risks as substantial as 60% [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 17 ] Numerous studies have shown that the routine use of JE vaccines consequences in a dramatic reduction of cases and incidence rates. [ 18 19 ] No disease sequel was found from 210 survivors of 2016 cases through the retrospective surveillance. Primary health care physicians play an important role in treatment of the JE disease.…”
Section: Discussionmentioning
confidence: 99%